Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the equation $\tan(x) = 2\sin(x)$ and I'd like to transform it in this way: $$\tan(x) = 2\sin(x) \Longleftrightarrow \frac{\sin(x)}{\cos(x)} = 2\sin(x) \Longleftrightarrow \sin(x) = 2\sin(x)\cos(x) \Longleftrightarrow \sin(x) = \sin(2x)$$ But I'm getting a wrong result so I suppose that I can't do it in this way. Why?

This is my solution: $$\tan(x) = 2\sin(x) \Longleftrightarrow \frac{\sin(x)}{\cos(x)} = 2\sin(x) \Longleftrightarrow \sin(x) = 2\sin(x)\cos(x) \Longleftrightarrow \sin(x) = \sin(2x) \Longleftrightarrow \sin(2x) - \sin(x) = 0 \Longleftrightarrow 2\cos(\frac{3x}{2})\sin(\frac{x}{2}) = 0 \Longleftrightarrow \cos(\frac{3x}{2}) = 0 \vee \sin(\frac{x}{2}) = 0$$

Proper solution is $\cos(x) = \frac{1}{2} \vee \sin(x) = 0$

share|cite|improve this question
I think he is trying to solve this equation; I am proceeding on that assumption. – ncmathsadist Mar 1 at 14:33
@paulgarrett - tdudzik is making use of the identity $$2\cos \theta\sin\phi = \sin(\theta+\phi) - \sin(\theta-\phi)$$ with $\theta = 3x/2$ and $\phi = x/2$ – Paul Sinclair Mar 1 at 17:38
@PaulSinclair, ok, and/but I more more largely baffled by the whole route taken, is the reason for my question. E.g., why not just take out the factor $\sin(x)$ in the first place, to have $\sin(x)\cdot (\cos x - 1)=0$ or whatever? All mysterious to me... – paul garrett Mar 1 at 17:51
@paulgarrett - certainly a much easier method, but this question was "what is wrong with this method?", not "how could I have done this more easily?". And there is actually nothing wrong with the path he chose, other than failing to go all the way. – Paul Sinclair Mar 1 at 18:09
@Shufflepants: If you do division by something that could be zero, that is illegal and punishable by contradiction. – user21820 Mar 2 at 5:19
up vote 12 down vote accepted

There is no problem. Your solution is correct, and the other solution is correct. But you need to do a little work to see that they give the same answers:

  • $\cos \frac {3x}2 = 0$ gives $x = \frac{(2k+1)\pi}3:\ x \in \{\pm \frac{\pi}3, \pm\pi,\pm \frac{5\pi}3, \pm \frac{7\pi}3, \pm 3\pi, \ldots\}$
  • $\sin \frac {x}2 = 0$ gives $x = 2k\pi:\ x \in \{0, \pm 2\pi, \pm 4\pi, \ldots\}$


  • $\cos x = \frac 12$ gives $x =\pm \frac{\pi}3 + 2k\pi:\ x \in \{\pm \frac{\pi}3, \pm \frac{5\pi}3, \pm \frac{7\pi}3, \ldots\}$
  • $\sin x = 0$ gives $x = k\pi:\ x \in \{0, \pm\pi, \pm 2\pi, \pm 3\pi,\pm 4\pi, \ldots\}$

Comparison of the values shows that the same ones are in both lists.

share|cite|improve this answer

You must disregard all points where $\cos(x) = 0$. These are outside of the domain of the initial expression you have on the left-hand side.

share|cite|improve this answer
Yeah, I know, but when I do this result will be correct? – tdudzik Mar 1 at 15:04
@tdudzik The result will be correct if there are any solutions where $\cos(x)\ne0$. – Simple Art Mar 2 at 0:07

The solutions to $\sin(\frac{x}{2})=0$ or $\cos(\frac{3x}{2})=0$ are given by $$\frac{x}{2} = \pi k \text{ or } \frac{3x}{2} = \frac{\pi}{2}+\pi k, k \in \mathbb Z,$$ which can be rewritten as $$x = 2\pi k \text{ or } x = \frac{\pi}{3}+\frac{2\pi}{3}k, k \in \mathbb Z.$$

The solutions to $\cos(x) = \frac{1}{2}$ or $\sin(x)=0$ are given by $$x = \frac{\pi}{3}+2\pi k, \frac{5\pi}{3}+2\pi k, \pi k, k \in \mathbb Z.$$ These are the same sets of points.

share|cite|improve this answer
Beat me by 5 seconds... – Paul Sinclair Mar 1 at 17:56
@PaulSinclair Hah, that does happen. +1 to you. :) – Dustan Levenstein Mar 1 at 18:01

Equations $\frac{\sin x}{\cos x} = 2\sin x$ and $\sin x =2\sin x\cos x$ are indeed equivalent since for $\cos x = 0$ you have $\sin x =\pm 1$, which doesn't give solution for the second equation.

So, to solve it, we have that either $\sin x = 0$ or $\cos x = \frac 1 2$, thus solutions are given by $x = 2k\pi$, $x = \pi + 2k\pi$, $x = \pm\frac\pi 3 + 2k\pi$, $k\in\mathbb Z$.

To summarize, there is no error in your manipulations.

share|cite|improve this answer

To solve, set $\sin(x) = \sin(2x) = 2\sin(x)\cos(x)$. Subtracting and factoring you get $$\sin(x)(2\cos(x) - 1) = 0.$$ This happens if $x = 0, \pi, \pi/3, 5\pi/3$. None of these is a solution to $\cos(x) = 0$, so they all work.

share|cite|improve this answer
I understand your solution but could you glance at my updated question and tell me what's wrong with my solution? – tdudzik Mar 1 at 17:01

There are two errors in your solution.

First, the transformation $$ \frac{\sin x}{\cos x} = 2\sin x \iff \sin x = 2\sin x \cos x $$ is false. The correct inference is $$ \left( \frac{\sin x}{\cos x} = 2\sin x \text{ and } \cos x \neq 0 \right) \text{ or } \cos x = 0 \iff (\sin x = 2\sin x \cos x \text{ and } \cos x \neq 0) \text{ or } \cos x = 0 $$ otherwise, going to the left, you divide by zero, and going to the right, you (might) delete the content of your equation by multiplying both sides by zero. (The hazards are $0 = 0 \implies 0 x = 0 y \not\Rightarrow x = y$ and $x \neq y \not\Rightarrow 0x \neq 0y \implies 0 \neq 0$.) Starting with either of your equations, you infer the entire other side of the more complicated bi-implication. Since this can introduce spurious solutions, all solutions must be checked in the original equation at the end of the process.

This suggests a general rule: Do not cancel. Instead subtract and factor. This highlights your second error. From $$ \sin x = 2 \sin x \cos x \text{,} $$ subtract and factor to get $$ (1-2\cos x)\sin x = 0 \text{.} $$ The first factor gives your $\cos x = \frac{1}{2}$. The second factor gives $\sin x = 0$. (This is because the product of several things being zero means at least one of them is.)

By proper inference, you should have \begin{align*} & & \tan x &= 2 \sin x \\ &\iff & \frac{\sin x}{\cos x} &= 2 \sin x \\ &\iff & \sin x &= 2 \sin x \cos x \text{ or } \cos x = 0 \\ &\iff & (1-2\cos x)\sin x &= 0 \text{ or } \cos x = 0 \\ &\iff & \cos x &= \frac{1}{2} \text{ or } \sin x = 0 \text{ or } \cos x = 0 \text{.} \end{align*} Checking for spurious solutions, all solutions of $\cos x = \frac{1}{2}$ and all solutions of $\sin x = 0$ are solutions of the given equation, but none of the solutions of $\cos x = 0$ are, so the final solution is $\cos x = \frac{1}{2} \text{ or } \sin x = 0$.

Somewhat shorter uses subtract and factor earlier, avoiding the complicated bi-implication altogether: \begin{align*} & & \tan x &= 2 \sin x \\ &\iff & \frac{\sin x}{\cos x} &= 2 \sin x \\ &\iff & \left( \frac{1}{\cos x} - 2 \right) \sin x &= 0 \\ &\iff & \frac{1}{\cos x} - 2 &= 0 \text{ or } \sin x = 0 \\ &\iff & \frac{1}{\cos x} &= 2 \text{ or } \sin x = 0 \\ &\iff & \cos x &= \frac{1}{2} \text{ or } \sin x = 0 \text{.} \end{align*}

share|cite|improve this answer
This strikes me as super confused. Your sequence of bi-implications after "By proper inference, you should have" are not correct at all; it should be "and $\cos x \neq 0$" after you've multiplied by $\cos x$. – Dustan Levenstein Mar 1 at 17:58
@DustanLevenstein : I could have "$(\sin x = 2 \sin x \cos x \text{ and } \cos x \neq 0) \text{ or } \cos x = 0$", exactly as in the prior bi-implication, but I invite you to show me how the set is changed by this complication. We cannot have either of $\cos x = 1/2 \text{ and } \cos x = 0$ or $\sin x = 0 \text{ and } \cos x = 0$. So the "$\dots \text{ and } \cos x \neq 0$" changes the set not at all. – Eric Towers Mar 2 at 23:57
What??? This is basic logic; "$\frac{\sin x}{\cos x} = 2 \sin x$" is equivalent to "$\sin x = 2 \sin x \cos x \text{ and } \cos x \neq 0$", not to "$\sin x = 2 \sin x \cos x \text{ or } \cos x = 0$" as you've said. I don't know why you nested the conditions on $\cos$; did you really misunderstand me that badly? – Dustan Levenstein Mar 3 at 1:01
Saying "... or $\cos x = 0$ introduces all solutions to $\cos x = 0$ to the set, none of which are solutions to the previous equation. – Dustan Levenstein Mar 3 at 1:03
@DustanLevenstein : "Since this can introduce spurious solutions, all solutions must be checked in the original equation at the end of the process." – Eric Towers Mar 3 at 1:07

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.